Information literacy as a social factor for understanding and inclusion in the world of work from the perspectives of Guy Le Boterf and Christine Bruce: introductory notes, necessary reflections - Araújo, Dos Santos Camila [UNESP]; Santos, Vanessa Cristina Bissoli [UNESP] (FapUNIFESP (SciELO), 2022)
The purpose of this article was to establish an analogy between the desirable professional profile of competences proposed by Le Boterf (2003) and the informed learning approach of Christine Bruce (2003, 2008) from the perspective of information literacy as a social factor of understanding and inclusion in the world of work. Based on a descriptive-exploratory bibliographical research, discussions were addressed regarding training, education, articulation, integration and mobilization of professional skills in view of the social demands of the world of work. It was about information literacy and its relationship with the world of work. Such approaches, when placed in a transversal logic and learning through experience, highlight the protagonism and empowerment of the individual's actions in a professional situation. The transversality of skills developed in the context of training for the world of work with information literacy articulates, integrates and mobilizes new skills, attitudes, values and knowledge with existing ones that support a holistic understanding in cultural, social, political, economic and temporal situations and professional actions, reflection, decision-making and problem solving by the individual based on the learning he acquires from his experiences and from his contact network.
Competência em Informação (CoInfo) como fator social de compreensão e inclusão ao mundo do trabalho sob as perspectivas de Guy Le Boterf e Christine Bruce: notas introdutórias, reflexões necessárias
Keywords: Employment inclusion; Information literacy; Professional skills; World of work